2021
DOI: 10.21203/rs.3.rs-910434/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Total Knee Arthroplasty to Treat Acute Knee Dislocation Associated With Osteoarthritis: a Case Report

Abstract: Background: Knee dislocation (KD) is a common disease in the young people. It is rare to report treatment of the KD associated with osteoarthritis (OA) in the old population. In this case report, we present two cases in which total knee arthroplasty (TKA) was performed to treat acute KD associated with osteoarthritis (OA) in two female patients. Methods: The two patients underwent knee injuries and limited range of motion (ROM). After diagnosing acute KD, including KD II and KD III-M, associated with OA with X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In a systematic review, Medina et al reported up to 18% of vascular injuries and up to 25% of nerve injuries [19]. Treatment guidelines for knee dislocation typically include reduction of the knee joint, stabilisation with external or internal fixation, reconstruction of injured neurovascular and ligamentous structures and rehabilitation procedures to restore joint function [12, 15, 24, 28, 37].…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review, Medina et al reported up to 18% of vascular injuries and up to 25% of nerve injuries [19]. Treatment guidelines for knee dislocation typically include reduction of the knee joint, stabilisation with external or internal fixation, reconstruction of injured neurovascular and ligamentous structures and rehabilitation procedures to restore joint function [12, 15, 24, 28, 37].…”
Section: Introductionmentioning
confidence: 99%